Visual analysis on the political orientation of historical characters in the Joseon Dynasty: Focusing on seo, Geojeong - Ha, Hyoji; Mun, Seongmin; Choi, Gyeongcheol; Hong, Eunbin; Lee, Sangkuk; Lee, Kyungwon (Archives of Design Research, 2019)
Background History studies involve the discovery of new facts based upon the records as well as understanding relationships between historic events and figures. However, a vast amount of resources, background knowledge and time would be required for empirical historical research. Visual analysis has the advantage of allowing users to easily identify the relationships between data. This study present a way to create and analyze human relationship visualizations using data from Genealogy of the Kwon family and the Annals of the Joseon Dynasty based on collaboration with historians, linguists and statisticians. Methods For the analysis, we used the bubble heap network visualization method, which expresses the similarities between the opinions of figures as distances between nodes. We also showed human relationships through the nodes' color and size. By looking at the relationship between kinship and political activities centered on Geojeong Seo, we explore the factors that influenced the formation of a relationship in the historical figure. In addition, our study shows the effectiveness of using visualization analysis tools in history data. Results Bubble heap network visualization enhanced the intuitive understanding by placing the figures needed to compare with Geojeong Seo based on similarities and expressing their kinship using the colors of nodes. This visualization also contributes to research in that it is easier to compare than other network visualizations as it facilitates the analysis by grouping figures with similarities. Conclusions In this study, we analyzed the voting similarity of Geojeong Seo and other figures. We also analyzed whether kinship affected the cause of voting similarity. As a result, historical events of the pre-modern period can be classified into state affairs, royal family, diplomacy, politics, and customs. The similarities between the Geojeong Seo and other figures are also different depending on the nature of the agenda. In addition, kinship cannot be regarded as an essential factor that affects the level of similarity of voting patterns.
Keywords: Historical data mining; Joseon-Dynasty; Network visualization; Visual analysis